Species-Specific Gene Expansion of the Cellulose synthase Gene Superfamily in the Orchidaceae Family and Functional Divergence of Mannan Synthesis-Related Genes in Dendrobium officinale - Wang, Yunzhu; Zhao, Kunkun; Chen, Yue; Wei, Qingzhen; Chen, Xiaoyang; Wan, Hongjian; Sun, Chongbo (Frontiers in Plant Science, 2022)
Plant cellulose synthase genes constitute a super gene family that includes the cellulose synthase (CesA) family and nine cellulose synthase-like (Csl) families, the members of which are widely involved in the biosynthesis of cellulose and hemicellulose. However, little is known about the cellulose synthase superfamily in the family Orchidaceae, one of the largest families of angiosperms. In the present study, we identified and systematically analyzed the CesA/Csl family members in three fully sequenced Orchidaceae species, i.e., Dendrobium officinale, Phalaenopsis equestris, and Apostasia shenzhenica. A total of 125 cellulose synthase superfamily genes were identified in the three orchid species and classified into one CesA family and six Csl families: CslA, CslC, CslD, CslE, CslG, and CslH, according to phylogenetic analysis involving nine representative plant species. We found species-specific expansion of certain gene families, such as the CslAs in D. officinale (19 members). The CesA/Csl families exhibited sequence divergence and conservation in terms of gene structure, phylogeny, and deduced protein sequence, indicating multiple origins via different evolutionary processes. The distribution of the DofCesA/DofCsl genes was investigated, and 14 tandemly duplicated genes were detected, implying that the expansion of DofCesA/DofCsl genes may have originated via gene duplication. Furthermore, the expression profiles of the DofCesA/DofCsl genes were investigated using transcriptome sequencing and qRT-PCR analysis, which revealed functional divergence in different tissues and during different developmental stages of D. officinale. Three DofCesAs were highly expressed in the flower, whereas DofCslD and DofCslC family genes exhibited low expression levels in all tissues and at all developmental stages. The 19 DofCslAs were differentially expressed in the D. officinale stems at different developmental stages, among which six DofCslAs were expressed at low levels or not at all. Notably, two DofCslAs (DofCslA14 and DofCslA15) showed significantly high expression in the stems of D. officinale, indicating a vital role in mannan synthesis. These results indicate that functional redundancy and specialization of DofCslAs with respect to polysaccharide accumulation. In conclusion, our results provide insights into the evolution, structure and expression patterns of CesA/Csl genes and provide a foundation for further gene functional analysis in Orchidaceae and other plant species.